2009
DOI: 10.1111/j.1651-2227.2009.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in children: inherited and acquired factors and age‐related variations in the presentation of 48 paediatric patients

Abstract: Our results emphasize that multiple predisposing risk factors commonly predispose to paediatric stroke. In addition, the primary clinical presentation appeared to differ between the older and younger children: hemiparesis was the typical presentation in children <1 year of age while seizure predominated in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
3
18
1
Order By: Relevance
“…Although seizures are often considered cortically based, and cortical infarcts have been identified as a risk factor for recurrent seizures (21), in our cohort several children with isolated subcortical infarcts had seizure on presentation. This observation is consistent with prior reports in children (21) and adults (19, 24, 35). Prior studies have reported that presence of seizures at presentation predicted involvement of the anterior circulation and cortical structures (9, 15, 17, 35).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although seizures are often considered cortically based, and cortical infarcts have been identified as a risk factor for recurrent seizures (21), in our cohort several children with isolated subcortical infarcts had seizure on presentation. This observation is consistent with prior reports in children (21) and adults (19, 24, 35). Prior studies have reported that presence of seizures at presentation predicted involvement of the anterior circulation and cortical structures (9, 15, 17, 35).…”
Section: Discussionsupporting
confidence: 94%
“…One study of 76 children with ischemic stroke aged 44 weeks to 19 years reported that children less than 1 year of age were significantly more likely to present with seizure (33). In contrast, a study of 48 children with ischemic and hemorrhagic stroke reported that children older than 1 year of age were more likely to present with seizures (19). Developmentally determined differences in neurotransmitter receptor composition, number, and distribution favor a state of enhanced excitability in immature versus mature brain (34).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, studies have suggested that Factor V Leiden and MTHFR mutations may be associated with increased risk of perinatal stroke[68]. On the other hand, a study examining polymorphisms of genes involved in the regulation of thrombosis and thrombolysis, and genes related to nitric oxide, cytokines, blood pressure control and cell adhesion did not find any differences in patients with perinatal arterial ischemic stroke compared to controls[5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found variable conclusions related to age, with one of the more significant studies identifying an age less than 3 years as significantly associated with seizure [37]. Some studies have variably seen increased incidence of seizures in patients less than 1 year of age [41] or greater than 1 year of age [42], and yet others have failed to identify any significant difference between age groups.…”
Section: Risk Factors For Seizures In Pediatric Strokementioning
confidence: 95%